An Analysis of Speech Functions used by Mr. Beast on Youtube Channel - Dhea, Fathiyah Rahma; azhari, andry (STBA Prayoga Padang, 2025)
Speech functions are ways used by someone to convey ideas in communication to make listeners understand the ideas correctly. According to Matthiessen and Halliday‟s (2014), there are four types of speech functions in communicating, namely statement, question, offer and command. Speech functions do not only occur in the real-life but also occurs in media such as YouTube. The purpose of this research is to analyze the speech functions used by Mr. Beast. Studying speech functions is important for effective communication, as understanding them allows one to convey messages clearly, understand messages received, and respond appropriately. This research was qualitative research. The researcher collected the data by using non-participant observation. The data were obtained from the YouTube channel of Mr. Beast. The data of this research are 4 Mr. Beast videos on YouTube channel that are the most popular in 2023, that are determined by looking at the highest number of viewers of each video. The analysis of the data was conducted according to Matthiessen and Halliday‟s theory (2014) of speech functions. This research was analyzed by organizing and preparing the data, watching the videos and reading the script, coding, representing data in a table. This research found all four types of speech functions on Mr. Beast YouTube channel with 191 data. The most dominant type is statement with 89 data, followed by questions with 58 data, below that there are commands with 30 data, and the lowest is offer with 14 data. It is hoped that this research can contribute to developing knowledge related to the field of linguistic especially about speech functions.